Diglosia y contacto lingüístico en Limón, Costa Rica - Aguilar-Sánchez, Jorge (2022)
This paper provides a description of the language contact situation in Limón, Costa Rica. It presents a theoretical account regarding language contact in this area and discusses why this linguistic situation leads to challenges for the definition of diglossia and bilingualism that have traditionally been used to describe it. The analysis concludes with support for the thesis that two varieties of English interact with a variety of Spanish in the Costa Rican area of Limón and result in a new variety of Spanish due to this language contact. This study highlights the need to explore these varieties of Spanish to fully understand this contact situation.